A Single‐Pot Template Reaction Towards a Manganese‐Based T1 Contrast Agent. Issue 19 (1st April 2021) - Anbu, Sellamuthu; Hoffmann, Sabrina H. L.; Carniato, Fabio; Kenning, Lawrence; Price, Thomas W.; Prior, Timothy J.; Botta, Mauro; Martins, Andre F.; Stasiuk, Graeme J.
Abstract: Manganese‐based contrast agents (MnCAs) have emerged as suitable alternatives to gadolinium‐based contrast agents (GdCAs). However, due to their kinetic lability and laborious synthetic procedures, only a few MnCAs have found clinical MRI application. In this work, we have employed a highly innovative single‐pot template synthetic strategy to develop a MnCA, MnL Me, and studied the most important physicochemical properties in vitro. MnL Me displays optimized r 1 relaxivities at both medium (20 and 64 MHz) and high magnetic fields (300 and 400 MHz) and an enhanced r 1 b =21.1 mM −1  s −1 (20 MHz, 298 K, pH 7.4) upon binding to BSA ( K a =4.2×10 3  M −1 ). In vivo studies show that MnL Me is cleared intact into the bladder through renal excretion and has a prolonged blood half‐life compared to the commercial GdCA Magnevist. MnL Me shows great promise as a novel MRI contrast agent. Abstract : We present a single‐pot template synthesis strategy for a manganese‐based MRI contrast agent, MnL Me . MnL Me is highly inert toward zinc‐transmetallation and displays enhanced T 1 relaxivity upon non‐covalent interaction with serum albumin. In vivo studies show higher contrast enhancement in the liver and longer blood half‐life than that of the commercially available contrast agent Magnevist. MnL Me shows great potential for use as a blood pool agent.